Control of electron-electron interaction in graphene by proximity screening - M. Kim (Nature Portfolio, 2020)
Experimental control of electron-electron interactions in materials is challenging. Here, the authors control the interactions by proximity screening with gate dielectrics of nanometer thickness, revealing qualitative changes in concentration and temperature dependences, and validating their analysis using electron hydrodynamics and umklapp scattering approaches.